A method for preparing a bifunctional water electrolysis catalyst with a high activity array structure
By preparing NiFe@NiFeCuOOH dual-function electrocatalyst, the problem of catalyst preparation under high temperature and high pressure conditions in the prior art is solved, and the electrocatalytic performance is achieved with high efficiency, low cost and controllability, which is suitable for industrial mass production and application.
Patent Information
- Application Number
- CN202310059017.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-01-13
AI Technical Summary
It is difficult to prepare a dual-function electrolytic water catalyst with high efficiency, low cost and controllability in the prior art, especially under high temperature and high pressure conditions, resulting in limited industrial mass production of catalysts.
Through the steps of foam copper treatment, copper hydroxide array electrode preparation, electrolyte configuration, electroplating, washing and drying, two in-situ reactions such as electrodeposition and chemical deposition were used to prepare NiFe@NiFeCuOOH dual-function electrocatalyst. The mild reaction conditions, low cost and easy-to-control characteristics of this method make it suitable for industrial mass production.
The prepared NiFe@NiFeCuOOH catalyst has high activity, good stability, and many catalytic active sites. It can efficiently catalyze hydrogen and oxygen evolution reactions in electrolytic water, and exhibit excellent electrocatalytic performance and stability in industrial applications.
Smart Images

Figure CN115852432B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrocatalyst preparation and catalytic chemistry, and relates to a method for preparing a bifunctional catalyst used for water electrolysis, and specifically to a method for preparing a bifunctional water electrolysis catalyst with a high-activity array structure. Background Art
[0002] With the development of society and the rapid growth of economy, the demand for energy has been increasing in recent years, which has caused a large consumption of fossil fuels such as coal and oil. The further consumption of these non-renewable energy sources has aggravated the arrival of the energy shortage crisis. At the same time, the burning of a large amount of fossil fuels has also led to serious environmental problems such as environmental pollution, intensified greenhouse effect, and global warming, which seriously affect people's daily life. With the emphasis of various countries on clean, renewable and environmentally friendly energy, it has become a global consensus to find an efficient, environmentally friendly and sustainable renewable energy. Among the various new energy sources being developed today, hydrogen, as a clean energy with high energy density and only water as combustion product, shows great development potential in the field of new energy. Among the many hydrogen production methods, water electrolysis hydrogen production as a novel green hydrogen production method has received widespread attention and research interest.
[0003] The overall reaction of water electrolysis is divided into the anode oxygen evolution reaction (OER) and the cathode hydrogen evolution reaction (HER). The high overpotential of the hydrogen evolution reaction and the oxygen evolution reaction consumes a lot of energy of the overall reaction, resulting in a decrease in hydrogen production. In order to solve this problem, efficient electrocatalysts are needed to accelerate the reaction kinetics. Currently, the efficient hydrogen and oxygen evolution catalysts that people are familiar with are the oxides of platinum metals and precious metals iridium and ruthenium, respectively. However, factors such as the scarcity of precious metal resources, high prices, and poor stability have severely restricted their large-scale application and development, so finding a cheap and efficient catalyst has become a research focus.
[0004] Generally speaking, due to the different reaction processes of hydrogen evolution reaction and oxygen evolution reaction, hydrogen evolution catalyst and oxygen evolution catalyst are not the same material. It is a challenge to prepare bifunctional catalysts with both high hydrogen evolution and high oxygen evolution activity. At present, the main methods for preparing bifunctional electrocatalysts are hydrothermal method, chemical vapor deposition method and low-temperature solid phase method. However, the high temperature and high pressure conditions lead to harsh preparation conditions, high energy consumption cost, long reaction cycle, and environmental problems caused by toxic substances produced during production. The inability to industrialize mass production has restricted the preparation of bifunctional electrocatalyst materials to a certain extent. Therefore, it is of great significance to develop a method for a bifunctional high-activity electrolytic water catalyst with simple synthesis process, low cost, good controllability and three-dimensional array structure. Summary of the invention
[0005] The present invention aims to overcome the deficiencies in the above prior art and provides a method for preparing a bifunctional water electrolysis catalyst with a high-activity array structure. The catalyst is prepared by sequentially undergoing copper foam treatment, copper hydroxide array electrode preparation, electrolyte configuration, electroplating, washing and drying. Based on two in-situ reactions, electrodeposition and chemical deposition, a NiFe@NiFeCuOOH bifunctional electrocatalyst with high activity for hydrogen and oxygen evolution is obtained. The whole process has mild reaction conditions, the production process is easy to control, the cost is low, the cycle is short, and it is easy to industrialize and mass produce. The prepared catalyst has many active sites and high catalytic activity.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A method for preparing a bifunctional water electrolysis catalyst with a high-activity array structure, characterized in that the preparation method is carried out in the following steps in sequence:
[0008] S1. Foam copper treatment
[0009] Cut the foam copper into 1cm*1cm pieces and ultrasonically clean them with 4M HCL and distilled water in turn;
[0010] S2. Preparation of copper hydroxide array electrode
[0011] Weigh 2-4 g of ammonium persulfate and 1-3 g of sodium hydroxide respectively and place them in a container to form a mixed solution, add 30 mL of deionized water and stir to fully dissolve them, and immerse the S1-treated copper foam in the mixed solution to obtain a copper hydroxide array electrode;
[0012] S3. Electrolyte configuration
[0013] Weigh 1-2 g of nickel sulfate and 0.5-1 g of ferric chloride respectively and place them in a reaction container, add 30 mL of distilled water thereto, and stir evenly to prepare an electrolyte;
[0014] S4. Electroplating
[0015] The copper hydroxide array electrode obtained in S2 is placed in the electrolyte of the reaction container S3, with the platinum electrode as the anode and the copper hydroxide array electrode as the cathode, the reaction container is heated to make the electrolyte temperature reach 50°C, and the NiFe@NiFeCuOOH three-dimensional array electrode is obtained by electroplating;
[0016] S5, washing and drying
[0017] The electrode obtained by S4 was washed with distilled water and anhydrous ethanol for 3 to 6 times in sequence, filtered, and the obtained electrode was placed in a drying oven for drying to obtain a highly active NiFe@NiFeCuOOH bifunctional electrocatalyst.
[0018] As a limitation of the present invention, in step S2, the temperature of the mixed solution for soaking the foam copper is 40° C., and the soaking time is 5 to 10 minutes.
[0019] In step S2, the treated copper foam is immersed in a mixed solution, and the copper foam is partially oxidized by ammonium persulfate to generate copper ions. At the same time, the generated copper ions react with OH - The copper hydroxide electrode array is continuously reacted and reacted in situ on the copper foam to form an array morphology. In this process, the concentration ratio of ammonium persulfate and sodium hydroxide, as well as the temperature and time of the reaction are crucial to the formation of the copper hydroxide electrode array morphology, which affects the reaction degree and reaction speed of the copper foam, as well as the process and morphology of the copper hydroxide array formation, which will determine the formation process of the final product in the subsequent electroplating process. In the present invention, the copper foam provides a copper source on the one hand, and also plays a supporting role as a catalyst substrate on the other hand. In the process of the copper foam forming the copper hydroxide array electrode in the mixed solution, it is necessary to ensure a sufficient copper ion generation rate and to controllably react with OH - The reaction forms a copper hydroxide array morphology. At the same time, the firmness and stability of the generated copper hydroxide electrode must be ensured to prevent it from growing too fast and causing agglomeration and collapse. Sufficient copper ions and OH are also required. - It can continuously react to generate an array structure to better provide a template for subsequent reactions and participate in the electroplating reaction process.
[0020] The soaking time in the present invention is 5 to 10 minutes, and the reaction degree and structural morphology of the copper hydroxide array structure can be well controlled within this time. In this process, when the temperature of the mixed solution exceeds 40°C, the reaction process will be more intense, the oxidation rate of the foamed copper and the speed of the copper ions combining with the hydroxide ions will be faster, the nucleation and growth of the copper hydroxide will be difficult to control, the copper hydroxide will grow in blocks and easily agglomerate and collapse, and the morphology of the array cannot be generated; when the temperature of the mixed solution is less than 40°C, the reaction process slows down, the copper hydroxide generation rate is slower, and the uniformity of the growth and distribution of the copper hydroxide array is poor, which directly affects the degree of participation in the reaction in the subsequent electroplating process, and further affects the morphology and performance of the final product.
[0021] As a second limitation of the present invention, in step S1, the time for ultrasonic cleaning with HCL is 10 minutes, and the time for ultrasonic cleaning with distilled water is 15 minutes.
[0022] In the present invention, stains and debris on the surface of the copper foam are cleaned by ultrasonic cleaning with HCL to prevent them from interfering with and affecting subsequent processes, and then the HCL is thoroughly cleaned with distilled water to prevent acid solution entrained in the copper foam from affecting subsequent processes.
[0023] As a third limitation of the present invention, in step S4, the current of the electroplating is 30-50 mA, and the electroplating time is 20 minutes.
[0024] In the electroplating process, the copper hydroxide array electrode not only acts as the cathode of the electroplating but also as a reactant to participate in the reaction process of the electroplating. Within the scope of the current and time of the present invention, a part of the nickel ions and iron ions can react with the copper hydroxide array electrode to generate NiFeCuOOH under the template effect of the copper hydroxide array electrode, and another part of the nickel ions and iron ions generate NiFe products, and are uniformly embedded in NiFeCuOOH while NiFeCuOOH is generated, and finally generate NiFe@NiFeCuOOH catalytic material. In the electroplating process, two reactions occur simultaneously, namely, the nickel-iron bimetallic material is prepared by electrodeposition, and the NiFeCuOOH three-dimensional electrode material is prepared by chemical deposition. This process requires better control of the concentration and reaction process of the reactants, and the current of the electroplating should not be too high or too low. On the one hand, the speed and degree of reaction are guaranteed to prevent the growth from forming agglomeration too fast, resulting in poor stability. On the other hand, it also affects the uniformity of the growth of the catalytic material, thereby affecting the catalytic performance of the final catalytic material.
[0025] As a fourth limitation of the present invention, in step S5, the drying temperature is 60-100° C., and the drying time is 6-12 hours.
[0026] The present invention has another limitation, that the highly active NiFe@NiFeCuOOH bifunctional electrocatalyst has a morphology of a three-dimensional array structure with uniform orientation, and the nanorods are several microns in length and 100 to 300 nanometers in diameter.
[0027] As is well known, the morphology of a material has an important influence on its catalytic performance. Since the hydrogen evolution and oxygen evolution processes in the process of hydrogen production by electrolysis of water are half-reactions of two different reaction processes, the NiFe@NiFeCuOOH bifunctional electrocatalyst of the present invention can have a good catalytic effect on both the hydrogen evolution process and the oxygen evolution process. The three-dimensional array structure morphology of the catalyst not only has good stability and many catalytic active sites, but also is conducive to the transmission of ions and electrons. The synergistic effect of NiFe and NiFeCuOOH formed in situ by the catalytic material of the present invention enhances the catalytic effect of oxygen and hydrogen evolution in the process of hydrogen production by hydrolysis.
[0028] The above-mentioned preparation method of the present invention as a whole, each step is closely related and inseparable, and they jointly affect the performance and morphology of the final product.
[0029] Due to the adoption of the technical solution of the present invention, the present invention has the following beneficial effects compared with the prior art:
[0030] 1. The reaction conditions of the present invention are mild, the production process is easy to control, the cost is low, the production cycle is short, and it is easy to promote and apply industrialization.
[0031] 2. The prepared catalytic electrode has a three-dimensional array structure with uniform orientation, which greatly increases the active sites and catalytic activity of the electrode. The synergistic effect of NiFe and NiFeCuOOH in the catalytic material enhances the catalytic effect of oxygen and hydrogen evolution in the process of hydrolysis to produce hydrogen, and the catalytic stability is high.
[0032] 3. When the catalytic material of the present invention is used as a hydrogen evolution electrode, the current density is 100 mA cm -2 The hydrogen evolution overpotential is -262mV, which has excellent electrocatalytic hydrogen evolution activity; when the material is used as an oxygen evolution electrode, the catalytic performance remains basically unchanged after 5000 cycles, and it has excellent catalytic stability.
[0033] The invention is suitable for preparing a bifunctional water electrolysis catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a scanning electron microscope image of the sample prepared in Example 1 of the present invention;
[0035] Figure 2 is an elemental analysis diagram of the sample prepared in Example 1 of the present invention;
[0036] Figure 3 is the electrocatalytic LSV diagram of the sample prepared in Example 2 of the present invention;
[0037] Figure 4 is an oxygen evolution cycle stability diagram of the sample prepared in Example 3 of the present invention;
[0038] Figure 5 is a scanning electron microscope picture of a sample prepared in Example 4 of the present invention at a high magnification;
[0039] Figure 6 This is a scanning electron microscope image of the sample prepared in Comparative Example 1 at a high magnification;
[0040] Figure 7 It is a comparison diagram of the LSV curves of the sample prepared in Example 4 of the present invention and the sample prepared in Comparative Example 2. DETAILED DESCRIPTION
[0041] Example 1 Preparation method of a highly active bifunctional water electrolysis catalyst with an array structure
[0042] The preparation method of the catalyst of this embodiment is carried out in the following steps in sequence:
[0043] S1. Treat the copper foam. Cut the copper foam into 1cm*1cm pieces and clean them with 4M HCL and distilled water for 10min and 15min respectively.
[0044] S2, weigh 2g of ammonium persulfate and 3g of sodium hydroxide into a beaker, add 30mL of deionized water and stir to fully dissolve them to form a mixed solution, soak the foam copper in step S1 in the mixed solution at 40°C for 10 minutes to obtain a copper hydroxide array electrode;
[0045] S3, weigh 2g of nickel sulfate and 1g of ferric chloride respectively, add 30mL of distilled water, and stir evenly to prepare an electrolyte;
[0046] S4, placing the copper hydroxide array electrode obtained in step S2 into the electrolyte of step S3, using the platinum electrode as the anode and the copper hydroxide array electrode as the cathode, heating the electrolyte temperature to 50° C., and electroplating for 20 min at a current of 50 mA to obtain a NiFe@NiFeCuOOH three-dimensional array electrode;
[0047] S5. Wash the electrode obtained in S4 with distilled water and anhydrous ethanol three times in sequence, filter, and dry the obtained electrode in a drying oven at 60° C. for 12 h to obtain a highly active NiFe@NiFeCuOOH bifunctional electrocatalyst.
[0048] Figure 1 This is a SEM image of the catalyst prepared in this example. From this image, we can see that the material is a typical three-dimensional array structure with uniform orientation. This structure is conducive to the transmission of ions and electrons, ensuring its good catalytic activity.
[0049] Figure 2 This is an elemental analysis diagram of the catalyst prepared in this example. From this diagram, it can be seen that the material is a bifunctional electrocatalyst of NiFe@NiFeCuOOH, proving that iron, nickel and copper ions successfully participate in the reaction.
[0050] Example 2 Preparation method of a high-activity array structure bifunctional water electrolysis catalyst
[0051] The preparation method of the catalyst of this embodiment is carried out in the following steps in sequence:
[0052] S1. Treat the copper foam. Cut the copper foam into 1cm*1cm pieces, and use 4M HCL and distilled water to ultrasonically clean them for 10min and 15min respectively, and set aside.
[0053] S2, weigh 3g of ammonium persulfate and 2g of sodium hydroxide into a beaker, add 30mL of deionized water and stir to fully dissolve them to form a mixed solution, soak the foam copper of S1 in the mixed solution at 40℃ for 8min to obtain a copper hydroxide array electrode;
[0054] S3, weigh 1.2g of nickel sulfate and 0.8g of ferric chloride respectively, add 30mL of distilled water, and stir evenly to prepare an electrolyte;
[0055] S4. Place the copper hydroxide electrode obtained in S2 into the electrolyte of S3, use the platinum electrode as the anode and the copper hydroxide array electrode as the cathode, heat the electrolyte temperature to 50°C, and electroplate for 20 minutes at a current of 40 mA to obtain a NiFe@NiFeCuOOH three-dimensional array electrode.
[0056] S5. Wash the electrode obtained in S4 with distilled water and anhydrous ethanol for 5 times in sequence, filter, and dry the obtained electrode in a drying oven at 80° C. for 8 h to obtain a highly active NiFe@NiFeCuOOH bifunctional electrocatalyst.
[0057] The electrode prepared in this example was used in water electrolysis to produce hydrogen and was used as a hydrogen evolution electrode. The current density of the test was 100 mA cm -2
[0058] Figure 3 The electrocatalytic LSV diagram of the sample prepared in the embodiment shows that at a current density of 100 mA cm -2 The hydrogen evolution overpotential of the material prepared in this example is -262 mV, indicating that the sample has excellent electrocatalytic hydrogen evolution activity.
[0059] Example 3 Preparation method of a highly active bifunctional water electrolysis catalyst with an array structure
[0060] S1. Treat the copper foam. Cut the copper foam into 1cm*1cm pieces, and use 4M HCL and distilled water to ultrasonically clean them for 10min and 15min respectively, and set aside.
[0061] S2, weigh 2g of ammonium persulfate and 1g of sodium hydroxide into a beaker, add 30mL of deionized water and stir to fully dissolve them to form a mixed solution, soak the foam copper of S1 in the mixed solution at 40℃ for 5min to obtain a copper hydroxide array electrode;
[0062] S3, weigh 1g of nickel sulfate and 0.5g of ferric chloride respectively, add 30mL of distilled water, stir evenly to prepare an electrolyte;
[0063] S4, placing the copper hydroxide electrode obtained in S2 into the electrolyte of S3, using the platinum electrode as the anode and the copper hydroxide array electrode as the cathode, heating the electrolyte temperature to 50°C, and electroplating for 20 minutes at a current of 30 mA to obtain a NiFe@NiFeCuOOH three-dimensional array electrode;
[0064] S5. Wash the above electrode with distilled water and anhydrous ethanol three times in sequence, filter, and dry the obtained electrode in a drying oven at 60° C. for 6 h to obtain a highly active NiFe@NiFeCuOOH bifunctional electrocatalyst.
[0065] The electrode prepared in this example was used in water electrolysis to produce hydrogen and as an oxygen evolution electrode. The current density of the test was 100 mA cm -2 , the oxygen evolution overpotential is 318mV.
[0066] Figure 4 : is the oxygen evolution cycle stability diagram of the electrode material. It can be seen from the figure that the catalytic performance of the catalyst prepared in this example remains basically unchanged after 5000 catalytic cycles, indicating that the prepared sample has excellent catalytic stability.
[0067] Example 4 Preparation method of a high-activity array structure bifunctional water electrolysis catalyst
[0068] S1. Treat the copper foam. Cut the copper foam into 1cm*1cm pieces, and use 4M HCL and distilled water to ultrasonically clean them for 10min and 15min respectively, and set aside.
[0069] S2, weigh 4g of ammonium persulfate and 3g of sodium hydroxide into a beaker, add 30mL of deionized water and stir to fully dissolve them to form a mixed solution, soak the foam copper of S1 in the mixed solution at 40℃ for 10min to obtain a copper hydroxide array electrode;
[0070] S3, weigh 2g of nickel sulfate and 1g of ferric chloride respectively, add 30mL of distilled water, and stir evenly to prepare an electrolyte;
[0071] S4, placing the copper hydroxide electrode obtained in S2 into the electrolyte of S3, using the platinum electrode as the anode and the copper hydroxide array electrode as the cathode, heating the electrolyte temperature to 50°C, and electroplating for 20 minutes at a current of 50 mA to obtain a NiFe@NiFeCuOOH three-dimensional array electrode;
[0072] S5. Wash the above electrode with distilled water and anhydrous ethanol for 6 times in sequence, filter, and dry the obtained electrode in a drying oven at 100° C. for 12 hours to obtain a highly active NiFe@NiFeCuOOH bifunctional electrocatalyst.
[0073] Figure 5 This is a high-magnification scanning electron microscope picture of the sample prepared in this embodiment. From this picture, it can be seen that the material array rod structure is obvious, the nanorod length is several microns, and the diameter is about 100-300 nanometers.
[0074] Comparative Example 1
[0075] This example prepares a water splitting electrocatalyst, similar to the preparation steps of Example 4, but uses a foam copper electrode as the electroplating cathode. This example is used as a comparative example to compare and analyze the copper hydroxide array electrode for the significant advantages of electrode array structure regulation and electrocatalytic performance improvement. The specific steps are as follows:
[0076] (1) Treating the copper foam: Cut the copper foam into 1 cm*1 cm pieces, and use 4M HCL and distilled water for ultrasonic cleaning for 10 min and 15 min respectively;
[0077] (2) Weigh 2 g of nickel sulfate and 1 g of ferric chloride respectively, add 30 mL of distilled water, and stir evenly to prepare an electrolyte;
[0078] (3) The copper foam obtained in step (1) is placed in the electrolyte of step 2, with the platinum electrode as the anode and the copper foam as the cathode. The electrolyte temperature is heated to 50° C. and electroplated at a current of 50 mA for 20 min to obtain a NiFe electrode.
[0079] (4) The electrode was washed with distilled water and anhydrous ethanol for 6 times in sequence, filtered, and the obtained electrode was placed in a drying oven at 100° C. for 12 h to obtain a NiFe electrocatalyst.
[0080] Figure 6 This is a scanning electron microscope picture of the sample of this embodiment at a high magnification; from this figure, it can be seen that the NiFe electrode catalyst structure synthesized in this embodiment is a spherical structure, and a bifunctional electrocatalyst with a three-dimensional array structure is not formed. In this comparative example, only an electrodeposition reaction occurs during the preparation of electroplating, thereby generating a NiFe electrocatalyst.
[0081] Comparative Example 2
[0082] In the present invention, metal-mediated synergistic catalysis plays an important role in improving the catalytic performance of hydrogen production by water electrolysis. In order to explore the effect of iron on the catalytic performance of the catalyst, the following catalyst was prepared in this example. The preparation process is similar to that of Example 4, except that no ferric chloride is added to the electrolyte.
[0083] The specific preparation steps of the catalytic material are as follows:
[0084] (1) Treating the copper foam: Cut the copper foam into 1 cm*1 cm pieces, and use 4M HCL and distilled water for ultrasonic cleaning for 10 min and 15 min respectively;
[0085] (2) Weigh 4 g of ammonium persulfate and 3 g of sodium hydroxide into a beaker, add 30 mL of deionized water and stir to fully dissolve them to form a mixed solution, soak the foam copper in step (1) in the mixed solution at 40° C. for 10 min to obtain a copper hydroxide array electrode;
[0086] (3) Weigh 2 g of nickel sulfate and add 30 mL of distilled water, stir evenly to prepare an electrolyte;
[0087] (4) placing the copper hydroxide electrode obtained in step (2) into the electrolyte of step (3), using the platinum electrode as the anode and the copper hydroxide array electrode as the cathode, heating the electrolyte temperature to 50° C., and electroplating for 20 minutes at a current of 50 mA to obtain a Ni@CuOOH three-dimensional array electrode.
[0088] (5) The electrode was washed with distilled water and anhydrous ethanol for 6 times, filtered, and dried in a drying oven at 100° C. for 12 h to obtain a Ni@CuOOH electrocatalyst.
[0089] In this embodiment, the electrolyte does not contain Fe 3+ , the Ni source cannot participate in the generation of hydroxyl nickel-copper substances during the electroplating process. This is mainly because without the addition of trivalent iron, the trivalent iron cannot undergo redox reaction with copper hydroxide to generate hydroxyl groups, thereby preparing the Ni@CuOOH electrocatalyst.
[0090] Figure 7 This is a comparison diagram of the LSV curves of the sample prepared in Example 4 of the present invention and the sample prepared in Comparative Example 2 (without the addition of ferric chloride). As can be seen from the figure, ferric chloride is not added to the electrolyte, and the catalyst performance prepared in this comparative example is significantly lower than that in Example 4, which indicates that the addition of ferric chloride plays a very important role in the preparation of highly active bifunctional electrocatalytic materials.
[0091] Comparative Example 3
[0092] This group of comparative examples prepared different types of electrocatalytic materials, and the specific process was as follows:
[0093] Group I: Catalytic material prepared in Example 4 of the present invention.
[0094] Group II: NiFe electrocatalyst, a catalytic material prepared in Comparative Example 1.
[0095] Group III: Catalytic material Ni@CuOOH electrocatalyst prepared in Comparative Example 2.
[0096] Group IV: The preparation process is similar to that of Example 4, except that: step S4 does not perform electroplating, and the prepared product is NiFeCuOOH material.
[0097] Group V: The preparation process is similar to that of Example 4, except that the mixed solution in step S2 is prepared by mixing sodium sulfate and sodium hydroxide.
[0098] Group VI: The preparation process is similar to that of Example 4, except that nickel foam is used in step S1, and the electrolyte in step S3 is a compound of copper sulfate and ferric chloride, and the prepared product is FeCu@FeNiCuOOH.
[0099] The materials prepared in Groups I to VII were subjected to a hydrolysis hydrogen production test. The electrochemical properties of the materials in the above groups were tested in a 6M potassium hydroxide solution as hydrogen evolution materials and oxygen evolution materials, respectively. The specific test was carried out according to the existing process (the same as the test process of the embodiment of the present invention). The current density of hydrogen evolution and oxygen evolution was 100 mA cm -2 The specific test data is shown in the following table.
[0100]
[0101] Finally, it should be noted that the above-described embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solution described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solution to deviate from the scope of the technical solution of the embodiments of the present invention.
Claims
1. A method for preparing a bifunctional water electrolysis catalyst with a high activity array structure, characterized in that: The preparation method is carried out in the following steps in sequence: S1. Foam copper treatment Cut the foam copper into 1 cm × 1 cm pieces, and clean them with 4M HCL and distilled water ultrasonically in turn for later use; S2. Preparation of copper hydroxide array electrode Weigh 2-4 g of ammonium persulfate and 1-3 g of sodium hydroxide respectively and place them in a container to form a mixed solution, add 30 mL of deionized water and stir to fully dissolve them, and immerse the foam copper treated with S1 in the mixed solution to obtain a copper hydroxide array electrode; S3. Electrolyte configuration Weigh 1-2 g of nickel sulfate and 0.5-1 g of ferric chloride respectively and place them in a reaction container, add 30 mL of distilled water thereto, and stir evenly to prepare an electrolyte; S4. Electroplating The copper hydroxide array electrode obtained in S2 is placed in the electrolyte of the reaction container S3, with the platinum electrode as the anode and the copper hydroxide array electrode as the cathode, the reaction container is heated to make the electrolyte temperature reach 50°C, and the NiFe@NiFeCuOOH three-dimensional array electrode is obtained by electroplating, the current of the electroplating is 30-50mA, and the electroplating time is 20min; S5, washing and drying The electrode obtained by S4 was washed with distilled water and anhydrous ethanol for 3 to 6 times in sequence, filtered, and the obtained electrode was placed in a drying oven for drying to obtain a highly active NiFe@NiFeCuOOH bifunctional electrocatalyst.
2. The method for preparing a bifunctional water electrolysis catalyst with a high activity array structure according to claim 1, characterized in that: In step S2, the temperature of the mixed solution for soaking the foam copper is 40° C., and the soaking time is 5 to 10 minutes.
3. The method for preparing a bifunctional water electrolysis catalyst with a high activity array structure according to claim 1, characterized in that: In step S1, the time of ultrasonic cleaning with HCL is 10 minutes, and the time of ultrasonic cleaning with distilled water is 15 minutes.
4. The method for preparing a bifunctional water electrolysis catalyst with a high activity array structure according to claim 1, characterized in that: In step S5, the drying temperature is 60-100° C., and the drying time is 6-12 hours.
5. The method for preparing a bifunctional water electrolysis catalyst with a high activity array structure according to claim 1, characterized in that: The highly active NiFe@NiFeCuOOH bifunctional electrocatalyst has a three-dimensional array structure with uniform orientation and a diameter of 100 to 300 nanometers.
Citation Information
Patent Citations
Electro-catalytic electrode and preparation method and application thereof
CN111676488A
Cu-based nano array composite nickel molybdenum oxide electrode material and preparation method and application thereof
CN113637999A